City profile of an ordinary secondary city of Eastern India: Raiganj City. (January 2022) - Basu, Tirthankar; Das, Arijit
Abstract: In recent times, the role of secondary cities is growing rapidly. It is observed that secondary cities in Latin America contribute nearly 25% of the country's GDP. Rapid urbanization in secondary cities is also noticed in developing South Asian countries. However, the investigations on the theme of urbanization and its associated facts largely remained concentrated to the large cities in these countries. Therefore, more studies are needed to perform on the urbanization character in secondary cities to address their immediate challenges and also to formulate adequate policies for sustainable development. This study selected a fast-growing ordinary city of Eastern India i.e. Raiganj City to highlight the different aspects of an ordinary city. This study revealed that the population has grown more than 10 times since the independence of the country. The existence of poor infrastructure mainly in the slum areas is a major challenge in this city. Besides, unplanned growth, a huge increase in traffic, and encroachment of part of the roads by illegal shops created several infrastructural problems. The infrastructural conditions at the household level are also not uniform. This study suggests an effective future spatial planning involving a future city planning map, Self Help Groups, and micro-enterprises. Highlights: The prime focus in urban science has always remained on the large cities. Studies on ordinary fast-growing secondary cities remained on low priority. This study tried to present the city profile of an ordinary secondary city in India. Through this, it tried to uncover the different aspects of the secondary cities. This study provided some suggestions for their sustainable development.